2019
DOI: 10.1002/nop2.288
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice towards care and maintenance of peripheral intravenous cannula among nurses in Chitwan Medical College Teaching Hospital, Nepal

Abstract: Aim The study is mainly concerned about the care and maintenance of peripheral intravenous cannulation: to determine the knowledge and practice of nurses towards care and maintenance of IV cannula and to find out the obstacles encountered in caring and maintaining IV cannula. Intravenous cannulation is a common procedure performed by nurses in every hospital and closely associated with the risk of nosocomial infections if standard care is not provided. Design A descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
4
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 20 publications
5
40
4
8
Order By: Relevance
“…However, the findings of present study were inconsistent with Al Yousef (2014) who found that internship nursing students had low level of performance regarding general measures of infection control standard precautions related to insertion of peripheral IV catheters and giving IV infusion. Also, the results of present study agreed with crosssectional studies done by Ghazali & Arbaee (2018) & Osti et al, (2019) to determine the knowledge and practice towards caring and maintaining peripheral IV cannula among nurses, they revealed that majority of them followed the correct practice of care and maintenance of peripheral IV cannula. However, these results were in disagreement with Qamar et al, (2017) in their study about assess nurses knowledge and practices towards care and maintenance of peripheral intravenous cannulation, as they found that nurses' practices are lacking as regard caring and maintenance of IV catheter.…”
Section: Ii: Internship Nursing Students' Knowledge About Infection Csupporting
confidence: 91%
“…However, the findings of present study were inconsistent with Al Yousef (2014) who found that internship nursing students had low level of performance regarding general measures of infection control standard precautions related to insertion of peripheral IV catheters and giving IV infusion. Also, the results of present study agreed with crosssectional studies done by Ghazali & Arbaee (2018) & Osti et al, (2019) to determine the knowledge and practice towards caring and maintaining peripheral IV cannula among nurses, they revealed that majority of them followed the correct practice of care and maintenance of peripheral IV cannula. However, these results were in disagreement with Qamar et al, (2017) in their study about assess nurses knowledge and practices towards care and maintenance of peripheral intravenous cannulation, as they found that nurses' practices are lacking as regard caring and maintenance of IV catheter.…”
Section: Ii: Internship Nursing Students' Knowledge About Infection Csupporting
confidence: 91%
“…• Using alcoholic chlorhexidine solution at > 0.5% or aqueous chlorhexidine at 2%. In cases of hypersensitivity, iodine solutions or alcohol at 70% may be used [4,17].…”
Section: Asepsismentioning
confidence: 99%
“…Nurses' knowledge on the proper management of PVC and early recognition of risk factors can reduce these complications [14,17]. In Spain, it is a nursing competence, collected in Order CIN/2134/2008, of 3 July [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu durumun PİK ve flebite ilişkin bilgi düzeyi yeterli olan ve olmayan hemşireler arasında farklı olmadığı saptanmamıştır. Benzer olarak, Osti ve ark (2019) yaptığı çalışmada, hemşirelerin çoğunluğu (%82.4) PİK'le ilgili doğru bilgiye sahip olmasına rağmen %68'inin kateter takıldıktan 72 saat sonra herhangi bir komplikasyon veya enfeksiyon belirtisi görülmese dahi kateteri değiştirdiği belirlenmiştir [20]. Qamar ve ark (2017) yaptığı çalışmada hemşirelerin PİK uygulama ve bakımına ilişkin bilgi düzeyleri yeterli bulunmasına rağmen %66.3'ünün kateter değişimlerini 72 saat sonunda yaptıkları, uygulamalarda eksiklikleri olduğu ve PİK'e ilişkin protokolleri yeterince takip etmedikleri belirlenmiştir [21].…”
Section: Pi̇k İzlemi Yapılan Hastaların Gi̇fs Puanlarına Göre Hemşirelerin Pi̇k Değişim Uygulamalarıunclassified